2005
DOI: 10.1007/s10038-005-0247-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tailor-made prevention of atherosclerosis with folic acid supplementation: randomized, double-blind, placebo-controlled trials in each MTHFR C677T genotype

Abstract: This study aimed at assessing the effect of folic acid supplementation quantitatively in each MTHFR C677T genotype and considered the efficiency of tailormade prevention of atherosclerosis. Study design was genotype-stratified, randomized, double-blind, placebocontrolled trials. The setting was a Japanese company in the chemical industry. Subjects were 203 healthy men after exclusion of those who took folic acid or drugs known to effect folic acid metabolism. Intervention was folic acid 1 mg/day p.o. for 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…These frequencies were similar to those reported in other Japanese subjects. 39 - 41 Although the present subjects consisted of visitors to an H. pylori clinic, the results may be extended to the general population in Japan.…”
Section: Discussionmentioning
confidence: 96%
“…These frequencies were similar to those reported in other Japanese subjects. 39 - 41 Although the present subjects consisted of visitors to an H. pylori clinic, the results may be extended to the general population in Japan.…”
Section: Discussionmentioning
confidence: 96%
“…19 Although still controversial, 20 the effect of folate supplementation in lowering Hcy levels has been demonstrated. [21][22][23][24] In addition, it has been recently shown that riboflavin (vitamin B 2 ) supplementation has a similar effect, 25 This gene-diet interaction has become even more interesting as riboflavin was associated with lowering blood pressure in hypertensive individuals with a TT genotype. 26 This example shows the need for thoroughly evaluating gene-diet interactions in randomized controlled clinical trials.…”
Section: Nutrigenetics: Dissecting the Genetic Architecture Of The Rementioning
confidence: 97%
“…Most genetic variations arise from single base pair changes referred to as single-nucleotide polymorphisms (SNPs), and can have substantial effects on an individual's health and susceptibility to disease. Using nutrigenetics, several genes have been identified with polymorphisms that alter the metabolism of nutrients such as folate and consequently susceptibility to nutrition-related chronic diseases including atherosclerosis and cardiovascular disease (Miyaki et al, 2005). Several vitamin D receptor (VDR) polymorphisms have been identified including VDR-Fok1, which is associated with reduced dietary calcium absorption, and VDR-Bsm1 and VDR-Apa1 associated with glucose intolerance and insulin resistance, respectively (Ames et al, 1999;Oh and Barrett-Connor, 2002;Smolders et al, 2009).…”
Section: Systems Biology Approaches To Nutritional Immunologymentioning
confidence: 99%